2018
DOI: 10.1080/19396368.2018.1450906
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid levels of anti-Müllerian hormone, insulin-like growth factor 1 and leptin in women with fertility disorders

Abstract: AMH: anti-Müllerian hormone; IGF1: insulin-like growth factor 1; PCOS: polycystic ovary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Similarly, others have noted this, although they regarded this group as a control group. 57,58 Another objective of our study was to determine the degree of oxidative stress in vivo in follicular fluid. Our results show some interesting differences between patients with PCOS, endometriosis, and TIF compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, others have noted this, although they regarded this group as a control group. 57,58 Another objective of our study was to determine the degree of oxidative stress in vivo in follicular fluid. Our results show some interesting differences between patients with PCOS, endometriosis, and TIF compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…(2018), выявлен более высокий уровень лептина в фолликулярной жидкости у женщин с ановуляторным бесплодием относительно пациенток, страдающих трубно-перитонеальным бесплодием, эндометриоз-ассоциированным бесплодием и необъяснимым бесплодием. По мнению авторов, данный показатель мог бы стать диагностическим маркером ановуляторного бесплодия [19].…”
Section: Discussionunclassified
“…As an indicator of this phenomenon, significantly altered level of serum AMH was reported by Seyhan et al ( 25 ) in endometriosis patients than healthy controls. In contradiction with this, Kucera et al ( 26 ) observed no differences in follicular fluid (FF) AMH levels between women with endometriosis and healthy control women. Several investigators have observed decreases in fertilization rate, yields of high-quality day 3 embryos, rates of blastocyst formation, and rates of implantation and pregnancy in IVF endometriosis patients compared to control subjects, and also in a mouse model of endometriosis embryotoxicity ( 24 , 27 30 ).…”
Section: Introductionmentioning
confidence: 92%